2008
DOI: 10.1212/01.wnl.0000336974.93499.ad
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Video Neuro Image : Chvostek sign with Fahr syndrome in a patient with hypoparathyroidism

Abstract: A 17-year-old short-statured girl (figure 1) presented with seizures, progressive cataracts, and tetany. Further evaluation revealed positive Chvostek sign (video), cerebrostriothalamic calcifications or Fahr syndrome, persistent hypocalcemia (total serum calcium 6.5 [normal 9 -10.5] mg/100 mL), and primary hypoparathyroidism (serum parathyroid hormone Ͻ3.0 [normal 12-72] pg/mL).Chvostek sign, seen in hypocalcemia, hypomagnesemia, or alkalosis, is also reported in children with epilepsy. 1 Calcifications in Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although this sign is very specific of hypocalcemia, it may also be present in up to 4% of the normal individuals (B). The Chvostek's sign is characterized by an ipsilateral contraction of the muscles around the lips or other facial muscles triggered by the tapping of the facial nerve over its trajectory anterior to the ear (89). This signal may be also positive in up to 10% of the normal individuals (D).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Although this sign is very specific of hypocalcemia, it may also be present in up to 4% of the normal individuals (B). The Chvostek's sign is characterized by an ipsilateral contraction of the muscles around the lips or other facial muscles triggered by the tapping of the facial nerve over its trajectory anterior to the ear (89). This signal may be also positive in up to 10% of the normal individuals (D).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Boller et al (12) reported calcification of the basal ganglion that demonstrated autosomal dominant inheritance in some cases. No genetic analysis for possible genes in this case, however, the family history did not suggest any possible genetic inheritance.…”
Section: Discussionmentioning
confidence: 99%